Experimental investigation and comparative analysis of immersion cooling of lithium-ion batteries using mineral and therminol oil. (5th May 2023) - Satyanarayana, G.; Ruben Sudhakar, D.; Muthya Goud, V.; Ramesh, J.; Pathanjali, G.A.
Graphical abstract: Highlights: Thermal management of Li-ion battery module using low-cost dielectric fluids. 43.83% reduction in maximum battery module temperature by forced air cooling. 49.17% & 51.54% reduction in maximum battery module temperature by using TOC & MOC. FAC method is satisfactory for discharge rates less than 1.5C. TOC & MOC proved to be a suitable coolant for discharge rates less than 2C. Abstract: Renewable energy can potentially mitigate the adverse effects of energy and environmental crises. The Lithium-ion battery, a storage system investigated in the present study, has a potential to increase the penetration of renewable energy technologies, due to its high mass and volumetric energy density. However, thermal management strategies are necessary for lithium-ion battery electrical storage to grow technologically and gain widespread acceptability. In the present work, a comparative study of the different cooling methods, namely, forced air cooling (FAC), direct liquid contact cooling (i.e., Mineral oil cooling (MOC), and therminol oil cooling (TOC)) with low-cost coolants have been carried out on 20 cells of 10Ah lithium-ion battery-stack at a discharge rate of 1C, 1.5C, 2C, 2.5C, and 3C. It is found that the maximum temperature of the battery module is reduced by 43.83%, 49.17%, and 51.54% for forced air cooling, therminol oil cooling, and mineral oil cooling respectively, at 3C discharge rate, compared to the natural air-cooling method. Under the experimental conditions studied, the maximum temperature of the battery pack is found to be within the desired value during forced convection cooling only up to 1.5C discharge rate, while the immersion cooling performed satisfactorily up to 2C discharge rate. This study demonstrates direct liquid contact cooling with low-cost dielectric fluids as a safe and efficient thermal management technology for high-energy density and high-current lithium-ion battery applications.